Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/alr.22099
|View full text |Cite
|
Sign up to set email alerts
|

Clinical associations between allergies and rapid eye movement sleep disturbances

Abstract: BackgroundAllergic rhinitis, an immunoglobulin E inflammatory condition including nasal congestion, obstruction, sneezing, pruritus, and fatigue symptoms, has significant impact on quality of life and impairs sleep. Sleep‐disordered breathing (SDB) patients often have normal all‐night apnea‐hypopnea (AHI) or respiratory‐disturbance (RDI) indices on polysomnography (PSG). We hypothesized that the rapid eye motion–respiratory disturbance index (REM‐RDI) may be a novel predictor of allergic status.MethodsA retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Sleep impairment has subsequent effects on daytime performance and HRQL. Moreover, the inflammatory cytokines released during allergic reactions have been related to the suppression of both rapid eyes movement (REM) and no‐REM phase [13, 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep impairment has subsequent effects on daytime performance and HRQL. Moreover, the inflammatory cytokines released during allergic reactions have been related to the suppression of both rapid eyes movement (REM) and no‐REM phase [13, 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, in children, SDB may negatively impact brain development, impair psychomotor, and cognitive performance, and contribute to hyperactivity 3338–3340 . REM sleep is associated with memory, cognition, dreams, and restorative sleep 1119,1147 . As the nasal cycle is prolonged, worsening nasal obstruction, people with AR have impaired REM sleep 1119,1147,3341–3343 .…”
Section: Associated Conditionsmentioning
confidence: 99%
“…The data on PSG parameters in adults is mixed. Most studies that perform PSG found that AR worsens PSG parameters 1103,1113–1122 ; however, two studies found either no difference or a modest change 1123,1124 …”
Section: Allergic Rhinitis Disease Burdenmentioning
confidence: 99%
“…5,6 Obstructive Sleep Apnea Airway collapses during the sleep cycle, preventing normal breathing, causing lack of oxygen to the brain, preventing the individual from reaching deep sleep along with body and brain repair. 1,5,6,13,14 Poor memory processing, poor emotion processing [2][3][4][5][6]9,12,37 out of the deep stages of sleep, they are prevented from obtaining rejuvenation of the body and brain needed to achieve or maintain optimal health. 1,2 Sleep arousals can be caused by poor sleep hygiene, restricted airway, systemic health issues, or cognitive health issues.…”
Section: Circadian Rhythm Disruptionsmentioning
confidence: 99%